MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN TWO STAY TWO STRAY SISWA KELAS X-AK SMK BHUMI PAHALA PARAKAN TEMANGGUNG - Anista Novi Yuswardani; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
The purpose of this research is to increase motivation and mathematics achievement of students in class X-AK SMK Bhumi Phala Parakan Temanggung with cooperative learning model type Two Stay Two Stray (TSTS). Type Classroom Action Research. The subject class X-AK and object motivation and mathematics learning achievement. Techniques of data collection is using observation, tests, questionnair and documentation. The results after application of TSTS models, motivation and mathematics learning achievement has increased. This is indicated by the average percentage of angket result of student learning motivation by 59,20% pre-cycle, the first cycle of 63.50%, and 69.51% in the second cycle. Results of students mathematics learning achievement test, the average value of mathematics learning achievement at 58,23 pre cycle, the first cycle increased to 66,00 and the second cycle increased to 77,17.